Perceptions of Cluttering Among Communication Sciences and Disorders and Non Communication Sciences and Disorders Students. - Blanchet, Paul G.; Snyder, Greg (Perspectives of the ASHA Special Interest Groups, 2017)
Purpose: The aim of this study was to compare perceptions of cluttering of undergraduate Communication Sciences and Disorders majors with perceptions of non-majors. Method: A total of 79 undergraduate students served as participants; 37 students were Communications Sciences and Disorders majors enrolled in an introductory-level course. The other 42 students were recruited from nutrition courses in the Department of Family and Consumer Sciences. All students were provided with a written definition of cluttering and also viewed a short segment of an educational video. Students then rated a person who clutters on a variety of speech skills and personality scales. Results: Results revealed that the Communication Sciences and Disorders students rated a person who clutters as exhibiting a significantly more inappropriate speech rate than did the Family and Consumer Sciences majors. However, results revealed no significant group differences in ratings of any personality traits. Conclusions: Findings do not support the presence of relatively positive perceptions of cluttering among Communication Sciences and Disorders majors, at least not prior to coursework or clinical training. Further research is needed to replicate these findings with larger sample sizes, and to assess attitudes of these students before and after coursework and/or clinical training in fluency disorders.